Tanulás melletti munkavállalás a Debreceni Egyetemen - Horváth, Kitti; Kósa, Rita Diána; Makai, Vivien; Nagy, Péter; Oláh, Kornélia; Oláh, Tímea; Oláh-Pucsok, Eszter; Szeder, Dóra Valéria; Timkó, Anikó (METSZETEK Társadalomtudományi Folyóirat, 2014)
-